From Decision Supporter to Informed Surrogate: An Improved Approach to Enrolling Cognitively Impaired Subjects in Clinical Research...49th Annual Health Law Professors Conference, June 3-5, 2026, Atlanta, Georgia. (Journal of Law, Medicine & Ethics)
While supported decision-making for persons with dynamic cognitive impairment has been considered in the context of medical treatment, there has been little attention to its application in the context of enrolling cognitively impaired subjects in clinical research. The Common Rule allows enrollment permission from a Legally Authorized Representative, one empowered under institutional policy to provide consent for subjects lacking decision-making capacity, but many Legally Authorized Representatives lack knowledge of the person's values and preferences adequate to an ethically valid judgement about research enrollment. Supported decision-making and surrogate decision-making can be complementary as subjects transition between impairment stages, providing an opportunity to address ethical problems with the current practice of reliance on uninformed surrogates. Through designation of a supporter who is willing to serve through the progression of impairment, dementia patients choose their supporter and ultimate surrogate, engage with them on the issues that later give rise to requests to enroll the subject in research, and ensure that the surrogate will have knowledge of the values and preferences of the subject necessary to an ethically defensible substituted judgement. Legal frameworks can be adapted to provide recognition of research enrollment as an area of valid decision by supporters on behalf of beneficiaries.